Construction of an HLA Classifier for Early Diagnosis, Prognosis, and Recognition of Immunosuppression in Sepsis by Multiple Transcriptome Datasets - Chen, Zhen; Chen, Rui; Ou, Yangpeng; Lu, Jianhai; Jiang, Qianhua; Liu, Genglong; Wang, Liping; Liu, Yayun; Zhou, Zhujiang; Yang, Ben; Zuo, Liuer (Frontiers in Physiology, 2022)
Background: The effects of HLA genes in sepsis is still not been comprehensively understood. Methods: A systematical search was performed in Gene Expression Omnibus (GEO) and ArrayExpress databases from inception to September 10, 2021. Random forest (RF) and modiﬁed Lasso penalized regression were conducted to identify hub genes, thus constructed a prediction model, namely HLA classifier. ArrayExpress databases, as external validation, were utilized to evaluate its diagnostic, prognostic and predictive performance. Next, we systematically correlated the HLA classifier with immunological characteristics from multiple perspectives, such as immune-related cells inﬁltrating, pivotal molecular pathways, and cytokine expression. Finally, quantitative real-time polymerase chain reaction (qRT-PCR) was conducted to validate the expression level of HLA genes in clinical samples. Results: A total of 9 datasets comprising 1251 patients were included. Based on RF and modiﬁed Lasso penalized regression, 5 HLA genes (B2M, HLA-DQA1, HLA-DPA1, TAP1, and TAP2) were identified as hub genes, which were subject to construct an HLA classifier. In the discovery cohort, HLA classifier exhibited superior diagnostic value (AUC=0.997), performed better in predicting mortality(AUC=0.716) than clinical characteristics or endotypes. Encouragingly, similar results were observed in the ArrayExpress databases. Additionally, immune infiltration analysis reveal that B cells, activated dendritic cell, NK cells, T helper cells, and infiltrating lymphocyte (IL) are signiﬁcantly richer in HLA low-risk phenotypes, while Tregs and myeloid-derived suppressor cells (MDSC) are more abundant in HLA high-risk phenotypes. Subsequently, molecular pathways analysis uncover that cytokine cytokine receptor interaction (CCR), and antigen-presenting cell (APC) co-stimulation were signiﬁcantly enriched in HLA low-risk endotypes. Finally, the expression levels of several cytokines (IL-10, IFNG, TNF) were significantly different between the HLA subgroups, and the ratio of IL-10/TNF was signiﬁcantly positively correlated with HLA score in multi-transcriptome data. Results of qRT-PCR validated that higher expression level of B2M as well as lower expression level of HLA-DQA1, HLA-DPA1, TAP1, and TAP2 in sepsis samples compared to control sample. Conclusion: Based on 5 HLA genes, a diagnostic and prognostic model, namely HLA classifier, was established, which is closely correlated with responses to hydrocortisone and immunosuppression status and might facilitate personalized counseling for speciﬁc therapy.